Chst9 marks a spatially and transcriptionally unique population of Oprm1-expressing neurons in the nucleus accumbens - Emma Andraka; Robert A. Phillips, III; Kasey L. Brida; Jeremy J. Day (Addiction Neuroscience, 2024)
Opioids produce addictive, analgesic, and euphoric effects via actions at mu opioid receptors (µORs). The µOR is encoded by the Oprm1 gene and is expressed in multiple brain regions that regulate reward and motivation, such as the nucleus accumbens (NAc). Oprm1 expression in NAc medium spiny neurons (MSNs) mediates opioid place preference, seeking, and consumption. However, recent single nucleus RNA sequencing (snRNA-seq) studies have revealed that multiple subpopulations of NAc neurons express Oprm1 mRNA, making it unclear which populations mediate diverse behaviors resulting from µOR activation. Using published snRNA-seq datasets from the rat NAc, we identified a novel population of MSNs that express the highest levels of Oprm1 of any NAc cell type. Here, we show that this population is selectively marked by expression of Chst9, a gene encoding a carbohydrate sulfotransferase. Notably, Chst9+ neurons exhibited more abundant expression of Oprm1 as compared to other cell types, and formed discrete cellular clusters along the medial and ventral borders of the NAc shell subregion. Moreover, CHST9 mRNA was also found to mark specific MSN populations in published human and primate snRNA-seq studies, indicating that this unique population may be conserved across species. Together, these results identify a spatially and transcriptionally distinct NAc neuron population characterized by the expression of Chst9. The abundant expression of Oprm1 in this population and the conservation of these cells across species suggests that they may play a key functional role in opioid response and identify this subpopulation as a target for further investigation.